AN EVALUATION OF THE RECENTLY PROPOSED PALAEOZOIC GASTROPOD SUBCLASS EUOMPHALOMORPHA - Nutzel A. (My University, 2002)
The recently proposed subclass Euomphalomorpha Bandel and Fryda, 1998 was primarily based on an openly coiled, planispiral initial whorl. Here, the protoconch of Carboniferous euomphalids is described and figured in detail previously unknown. This protoconch comprises distinctly less than one planispiral whorl with an abrupt transition to the telecoconch. It is umbilicate or openly coiled. Umbilicate or bilaterally symmetrical protoconchs are still present in Recent species of the Cocculiniformia, the Neomphalidae and the Docoglossa. A previously suggested close phylogenetic relationship between the euomphalids and primitive gastropod limpets is therefore corroborated by the protoconch morphology. The fact that several Palaeozoic gastropods, unlike most modern gastropods, have an openly coiled initial whorl is highly remarkable, but the meaning of this feature for the phylogeny and the systematics of the Gastropoda is not yet clear.
Keywords: GASTROPODA; SYSTEMATICS; PHYLOGENY; PALAEOZOIC; EUOMPHALIDAE; COCCULINIFORMIA; ARCHAEOGASTROPODA; Carboniferous; Paleozoic::Carboniferous; Палеозой::Каменноугольная